Preface: Special topic on chemical physics of ionic liquids - Perkin, S; Kirchner, B; Fayer, MD (American Institute of Physics, 2018)
Over the past several decades, since their reappearance in the literature, ionic liquids have progressed from being a curiosity to one of the most studied materials in the physical sciences today. This tremendous attention from researchers across many fields arises from emerging applications of ionic liquids in synthesis (templated nanomaterials synthesis, biowaste processing), engineering (lubrication, damping, heat transfer), and electrochemical devices (batteries, supercapacitors), amongst others. As these applications mature the need for detailed understanding and predictive capability becomes progressively more important. Responding to this need, a great deal of effort is now being invested in resolving molecular-scale details of structure, dynamics, and interactions in ionic liquids. This Chemical Physics of Ionic Liquids is a rich and diverse field, employing many experimental and theoretical approaches and extending its reach towards understanding a widening array of ionic materials.